New Attorney Swearing In Ceremony Held in State Building Auditorium - Watkins, Howard::::::::: (1987)
District 5 State Bar Board of Governor Dennis Cornell speaking at lectern; on stage: Superior Court Judge Blaine Pettitt, Justices Hollis Best, Robert Martin, Donald Franson, George Brown (Presiding), Wickson Woolpert, Charles Hamlin and Jay Ballantine